2017
DOI: 10.1159/000485174
|View full text |Cite
|
Sign up to set email alerts
|

Successful Subcutaneous Allergen-Specific Immunotherapy in Refractory Atopic Keratoconjunctivitis: A Case Report

Abstract: Purpose: We report a case of refractory atopic keratoconjunctivitis (AKC) which was successfully treated with subcutaneous immunotherapy (SCIT). Case Report: A 22-year-old woman presented with severe allergic conjunctivitis for one and a half year. She failed to respond to conventional topical anti-allergic medications, topical corticosteroid, as well as topical cyclosporine A. Therefore, oral corticosteroids had to be prescribed to control the exacerbation for 1 year. Due to refractory AKC and to avoid long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that improvements can be observed within 3 months after initiation of therapy, and those benefits may be long lasting with decreases in seasonal symptoms and use of anti-allergic medications, which further persisted for at least 2 years even after discontinuation of immunotherapy (115,116). A case study of apatient with atopic keratoconjunctivitis revealed that SCIT was fairly successful in controlling the allergic symptoms and disease exacerbation (117). The therapeutic benefits of SCIT are attributed to different types of regulatory mechanisms.…”
Section: Routes Of Administration In Aitmentioning
confidence: 99%
“…Previous studies have demonstrated that improvements can be observed within 3 months after initiation of therapy, and those benefits may be long lasting with decreases in seasonal symptoms and use of anti-allergic medications, which further persisted for at least 2 years even after discontinuation of immunotherapy (115,116). A case study of apatient with atopic keratoconjunctivitis revealed that SCIT was fairly successful in controlling the allergic symptoms and disease exacerbation (117). The therapeutic benefits of SCIT are attributed to different types of regulatory mechanisms.…”
Section: Routes Of Administration In Aitmentioning
confidence: 99%